Mangrove diversity and its relationships with environmental conditions in Kuala Bubon Village, West Aceh, Indonesia - WINTAH WINTAH; KISWANTO KISWANTO; ENDANG HILMI; MOH. HUSEIN SASTRANEGARA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wintah, Kiswanto, Hilmi E, Sastranegara MH. 2023. Mangrove diversity and its relationships with environmental conditions in Kuala Bubon Village, West Aceh, Indonesia. Biodiversitas 24: 4599-4605. Mangrove ecosystem plays various ecological and socio-economic roles. Indonesia has the largest extent of mangrove forest one of which is located in West Aceh Regency, Aceh Province. The aim of this study was to assess the diversity and structure of mangrove forest in Kuala Bubon Village, West Aceh, and to analyze the relationships between the existence of mangrove species and the environmental conditions. Field survey was conducted from May to August 2022 using plot sampling method on three stations representing various habitat characteristics. Vegetation sampling using a 10 x 10 m2 plot as well as measurement on physical parameters (pH, salinity, and temperature) and chemical parameters (sediment texture and organic carbon content) were conducted. The relationship between the presence of mangrove species and the environmental parameters was analyzed using Principal Component Analysis (PCA). The result of vegetation sampling recorded 6 mangrove species, i.e., Rhizophora stylosa Griff, Sonneratia alba Sm, Avicennia marina (Blume), c, and Sonneratia caseolaris (L) Engl. This study revealed that the presence of Rhizophora stylosa Griff was related to the conditions of the clay substrate, pH and temperature values. Meanwhile, the existence of Rhizophora apiculata Blume, Rhizophora mucronata Lamk, Sonneratia alba Sm, Sonneratia caseolaris (L) Engl, and Avicennia marina (Blume) was related to the conditions of the silt substrate, diameter and salinity. Based on the results of relationship analysis, silt substrate and salinity have a correlation to maintain the mangrove ecosystem.